Robert Kroetsch’s Verbal Parody of The Studhorse Man in Seed Catalogue - Dueck, Nathan (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
Demeter Proudfoot, the first-person narrator in Robert Kroetsch’s The Studhorse Man (1969), borrows from the techniques of oral storytellers, and the unnamed speaker of Kroetsch’s Seed Catalogue (1977) borrows Demeter’s penchant for fragments, repetitions, and set phrases that Demeter uses. The resulting metafiction — that is, writing that simultaneously reads itself — simulates the experience of reading aloud — that is, speaking that simultaneously listens to itself. Whereas The Studhorse Man parodies the oral tradition by collecting intertexts, challenging narrative conventions, and commenting on the act of storytelling, Seed Catalogue parodies the verbal expression within that novel. Moreover, the long poem performs its own interpretation through a “poet” speaker who appears to anticipate the response of readers, and provokes us to utter words we normally read to ourselves. Such a reading practice materializes the compositional method in Seed Catalogue.